SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN LOKASI CAFE BARU SUNCAFE SEBAGAI DESTINASI WISATA KULINER DI KABUPATEN PRINGSEWU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Arif Hidayat; Muhamad Muslihudin; Indah Tri Utami (LPPM STMIK Pringsewu, 2016)
District Pringsewu is growing districts that continue to make the development of various sectors, one of the tourism sector. Culinary tourism in the District Pringsewu growing quite rapidly, has a lot of standing places that sell a lot of food choices, from street vendors to modern eating places like cafes. Many cafe in the district of Pringsewu would be a separate issue in determining the appropriate location for the new cafe location Suncafe, for it needed a system that could help determine the location of a new cafe. The criteria used in making this decision support system include building area, spacious parking, accessibility, security, distance to the city center, the price of the location, and comfort. Decision support system is made using a simple additive weighting method (SAW) is looking for a weighted sum of the performance of each alternative. While the implementation of the program for decision support system is made by using Delphi 7. Obtained big 3 ranking the final results to determine the location of a new cafe, namely 1. Subdistrict of Pagelaran with a value of 80, 2. Subdistrict of Gadingrejo with a value of 79, and 3. Subdistrict of Adiluwih with a value of 78.55.